Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape. Issue 8 (1st August 2015) - Hammerschlag, Neil; Broderick, Annette C.; Coker, John W.; Coyne, Michael S.; Dodd, Mark; Frick, Michael G.; Godfrey, Matthew H.; Godley, Brendan J.; Griffin, DuBose B.; Hartog, Kyra; Murphy, Sally R.; Murphy, Thomas M.; et al.
Abstract : The "landscape of fear" model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.